’Hard translation’ in Stories to Enlighten the World - Wang, Aiqing (LingTera, 2023)
An illustrious figure of Ming-Qing fiction, Feng Menglong (1574-1646), compiled and edited a thought-provoking trilogy of short story anthologies towards the demise of the Ming (1368-1644) dynasty, which contributes to the thriving development of vernacular fiction. The first fascicle of the trilogy is an anthology entitled Stories Old and New (and subsequently Stories to Enlighten the World) that was published in 1620 and translated by Cyril Birch in 1958. In this research, I explore Birch’s rendering that has not attained enough academic attention. I propound that the translation abounds with literal translations and transliterations, which is consistent with the approach of "˜hard translation’ advocated by a renowned writer and translator Lu Xun, aka Zhou Shuren (1881-1936). The "˜hard translation’ strategies can be embodied by Birch’s translation of expressions pertaining to historical personages, religious and literary allusions, as well as sayings and idioms. Furthermore, Birch enriches literal translation and transliteration with illuminating notes and adopts the strategy of adaptation, so as to strike a balance between faithfulness and fluency.